Brain consequences of acute kidney injury: Focusing on the hippocampus - Maryam Malek (The Korean Society of Nephrology, 2018)
The high mortality rates associated with acute kidney injury are mainly due to extra-renal complications that occur following distant-organ involvement. Damage to these organs, which is commonly referred to as multiple organ dysfunction syndrome, has more severe and persistent effects. The brain and its sub-structures, such as the hippocampus, are vulnerable organs that can be adversely affected. Acute kidney injury may be associated with numerous brain and hippocampal complications, as it may alter the permeability of the blood-brain barrier. Although the pathogenesis of acute uremic encephalopathy is poorly understood, some of the underlying mechanisms that may contribute to hippocampal involvement include the release of multiple inflammatory mediators that coincide with hippocampus inflammation and cytotoxicity, neurotransmitter derangement, transcriptional dysregulation, and changes in the expression of apoptotic genes. Impairment of brain function, especially of a structure that has vital activity in learning and memory and is very sensitive to renal ischemic injury, can ultimately lead to cognitive and functional complications in patients with acute kidney injury. The objective of this review was to assess these complications in the brain following acute kidney injury, with a focus on the hippocampus as a critical region for learning and memory.